Encephalitis With Antibodies Against the GABAB Receptor: High Mortality and Risk Factors - Lin, Jingfang; Li, Chen; Li, Aiqing; Liu, Xu; Wang, Rui; Chen, Chu; Zhou, Dong; Hong, Zhen (Frontiers in Neurology, 2019)
Objective: To measure mortality, identify predictors of death and investigate causes of death in patients with anti-gamma-aminobutyric-acid B receptor (anti-GABABR) encephalitis. Methods: Prospective analysis of anti-GABABR encephalitis cases diagnosed between June 2013 and August 2018 in West China Hospital of Sichuan University, with assessment of factors associated with mortality. Results: A total of 28 patients (11 females) with anti-GABABR encephalitis were included in this study. After a maximum time of 52 months (median 11 months, range 2–52) of follow-up, 9 (32.1%) patients died, with a median survival time of 6.5 months. Five patients died of tumor progression, one patient died of convulsive status epilepticus, one patient died of septic shock, and two patients died of severe pneumonia. Predictors of death were older age at onset (P=0.025), presence of a tumor (66.7% vs 15.8%, P=0.013), the number of complications (2.6 vs 1.0, P=0.009) and deep venous thrombosis (33.3% vs 0, P=0.026). Conclusion: Patients with GABABR encephalitis have a high mortality rate within 5 years. Older age at onset, presence a tumor, the number of complications and deep venous thrombosis are associated with death.